1992
DOI: 10.1115/1.2891373
|View full text |Cite
|
Sign up to set email alerts
|

Strip Extensiometry for Comparison of the Mechanical Response of Bovine, Rabbit, and Human Corneas

Abstract: Specimens of bovine, rabbit, and human corneas were systematically tested in uniaxial tension to experimentally determine their effective nonlinear stress-strain relations, and hysteresis. Cyclic tensile tests were performed over the physiologic load range of the cornea, up to a maximum of 10 percent strain beyond slack strain. Dimensional changes to corneal test specimens, due to varying laboratory environmental conditions, were also assessed. The measured stress-strain data was found to closely fit exponenti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
159
0
4

Year Published

1997
1997
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 224 publications
(181 citation statements)
references
References 0 publications
13
159
0
4
Order By: Relevance
“…A more direct comparison was made by extracting the stress-strain response from our first preconditioning cycle. This un-preconditioned data (triangles in Figure 2.7) exhibited similar behavior to the bovine experiments reported in [35]. Unlike the present preconditioning methodology, simple single-ramp experiments combine recoverable viscoelastic strain with inelastic strain.…”
Section: Discussionsupporting
confidence: 67%
See 3 more Smart Citations
“…A more direct comparison was made by extracting the stress-strain response from our first preconditioning cycle. This un-preconditioned data (triangles in Figure 2.7) exhibited similar behavior to the bovine experiments reported in [35]. Unlike the present preconditioning methodology, simple single-ramp experiments combine recoverable viscoelastic strain with inelastic strain.…”
Section: Discussionsupporting
confidence: 67%
“…of cornea tensile strips from this study and Refs. [35,45] and in the vicinity of 10%/min. Tensile strip experiments of bovine corneas have shown that the tissue exhibits a nonlinear rate-dependent stress-strain response and a highly nonlinear creep response that depends on the applied hold stress.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…The uniaxial tensile tests are done using rectangular corneal strips subjected to tensile loading [1][2][3][4][5][6][7][8]. Because of the well-known limitations of this testing technique [9], it has often been used for comparative studies [3,6,10].…”
Section: Introductionmentioning
confidence: 99%